(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
India stands at the 33rd position in the list of most polluted country in the world.1 According to article published by “The Hindu” in the year 2015 India has overtaken China’s air pollution levels in 2015 and the average particulate matter exposure was higher for the first time in the 21st century2 and 80% of India’s surface water may be polluted, report by international body.3 And today the world is filled with various kinds of product. With the growing population the demands for the products have also increase. This has led to the growth of industries across the globe. And with the phase at which industrialization and urbanization has increased the environmental issues have also been increased. Today we live in the world where from the water we drink to the air we breathe is polluted. This has led to the outbreak of various disease. Therefore it becomes the responsibility the organizations as well as the consumers to contribute towards the betterment of the environment. Has an imitative many company have started to follow the concept of “Green Marketing”, where the organizations have started to manufacture product that are environment friendly products. But the question arise that whether consumers are ready to accept these product and if there are aware of the green marketing Hence in this paper “Impact of green marketing on consumer buying decision” aims at answering the questions; Does green marketing have any influence on the consumer buying decision? Do consumers are aware of the companies that are following green marketing strategies?